Best Clinical Practices with ATX-101 for Submental Fat Reduction: Patient-related Factors and Physician Considerations. Issue 7 (12th July 2021) - Teller, Craig F.; Chiu, Annie; Chesnut, Cameron D.; Sherman, Deborah; Raul Montes, José; Gaspard, Sara; Keaney, Terrence; Sadick, Neil S.; Yoelin, Steve; Sangha, Sara; Shridharani, Sachin M.
Abstract : Background: Submental fat can be reduced with ATX-101 (deoxycholic acid injection), a customizable and minimally invasive alternative to liposuction. In the years since its approval, the treatment patterns of ATX-101 have evolved. Methods: A panel of experienced physicians from the United States gathered to generate best practices for the use of ATX-101 in submental contouring. Results: The expert panel provided their insights on appropriate patient selection, managing patient expectations of ATX-101 treatment outcomes, and adverse events, and guidance on ATX-101 administration for optimal outcomes are presented here. Conclusion: These best clinical practices on the use of ATX-101 for the reduction of submental fat should enable physicians to enhance the patient treatment experience and outcomes.